The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s12544-019-0365-5
|View full text |Cite
|
Sign up to set email alerts
|

Combining ITS and optimization in public transportation planning: state of the art and future research paths

Abstract: Intelligent Transportation Systems (ITS) applications in public transportation have allowed for automated data collection, which is particularly useful for planning and operations. While technological advancement of ITS has so far been extensive, their usage for developing relevant planning and operational tools is rather limited. Research on planning and operations of public transportation systems has not widely investigated the potential of combining optimization models with data originating from ITS. Such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 117 publications
(276 reference statements)
0
29
0
1
Order By: Relevance
“…Xiaolei et al [11] demonstrated a data-mining procedure using transit data for Beijing, China. Christina and Konstantinos [12] argued in favor of combining optimization models with data originating from information technology services (ITS). Rosario et al [13] reviewed the advancement of emergent technologies, and their implementations and applications with respect to smart power grids and cities.…”
Section: Related Studiesmentioning
confidence: 99%
“…Xiaolei et al [11] demonstrated a data-mining procedure using transit data for Beijing, China. Christina and Konstantinos [12] argued in favor of combining optimization models with data originating from information technology services (ITS). Rosario et al [13] reviewed the advancement of emergent technologies, and their implementations and applications with respect to smart power grids and cities.…”
Section: Related Studiesmentioning
confidence: 99%
“…Iliopoulou and Kepaptsoglou [8] have presented a detailed literature review of usage of ITS data from public transportation for planning and decision making. Especially from the tactical planning perspective, the availability of AVLS and ETM data helps improve the OD demand estimation and thereby timetable design.…”
Section: Literature Surveymentioning
confidence: 99%
“…1) is a challenge and needs to be addressed on a case-by-case basis. This issue is surveyed in detail under the data quality considerations topic of Iliopoulou and Kepaptsoglou [8].…”
Section: Lack Of Standardization Across Data Sources and Formatsmentioning
confidence: 99%
See 1 more Smart Citation
“…T HE combination of timetable information and Automatic Fare Collecting systems (AFC) is being used more broadly by researchers and practitioners to understand public transportation on the strategic, tactical and operational level [1], [2], [3]. This has lead to the identification of issues with the data used [1], [2], [3], [4], [5], [6], [7]. It has been shown that buses using AVL can have errors due to broken GPS units (hardware error), the bus deviating from the scheduled route (operational error) or busses not uploading data (data error) [5], which can lead to the travellers having the wrong alighting stop stored [4].…”
Section: Introductionmentioning
confidence: 99%